Analisis Halal Critical Control Points (HCCPs) dan Residu Alkohol Minuman Kombucha pada UMKM XYZ - Nurafi Razna Suhaima; Aulia Irhamni Fajri (Jurnal Ilmiah Pangan Halal, 2026)
Kombucha is a tea-based fermented beverage that naturally generates ethanol as a byproduct of microbial activity. In halal product assurance, controlling residual ethanol and identifying Halal Critical Control Points (HCCPs) are essential to ensure halal compliance and product stability. This study aimed to determine HCCPs in materials and production processes at the SME (Small and Medium Enterprises) level and to evaluate residual ethanol at post-production and after one month of storage at ≤4℃ (chiller). Ethanol content was analyzed using Gas Chromatography–Flame Ionization Detection (GC-FID). The results indicated that sugar, SCOBY culture, cleaning agents, and packaging materials were categorized as critical material points, while fruits and rhizomes were not. Critical process points were identified during fermentation monitoring, packaging, and storage. Residual ethanol at post-production was 0.26% (w/w), below the <0.5% limit required for halal certification based on BPJPH (Halal Product Assurance Organizing Agency). However, after one month of chiller storage, ethanol increased to 0.55% (w/w), indicating continued fermentation. These findings highlight the importance of post-production control in maintaining ethanol stability and supporting halal supply chain integrity in kombucha production.